Gut microbiota metabolite acetate mediates free fatty acid receptor 2 expression to alleviate atopic dermatitis - Ye, Siqi; Wang, Jingwen; Luo, Feng; Jia, Jinjing; Mo, Xiumei; Chen, Dacan (Frontiers in Microbiology, 2025)
IntroductionPrevious studies have demonstrated that gut microbiota and its metabolites, short-chain fatty acids (SCFAs), are involved in the inflammatory manifestations and immune regulation of atopic dermatitis (AD). However, their potential associations and mechanisms remain unclear.MethodsThis study used antibiotics to construct a mouse model to analyze the performance of AD mice after gut microbiota destruction. 16S rRNA amplicon sequencing combined with HM700 high-throughput metabolomics was used to characterize differential microbial components and key metabolites in fecal specimens of AD murine models. Moreover, the mechanism of action of the key metabolite was investigated.ResultsAfter antibiotic treatment, AD murine models demonstrated exacerbated clinical manifestations, characterized by enhanced dermatitis severity, significant ear edema, and elevated inflammatory responses. 16S rRNA sequencing revealed significant changes in the Bacteroidetes/Firmicutes ratio, while HM700 identified acetate as an important regulatory metabolite in AD mice. Acetate supplementation in AD mice significantly ameliorated 2,4-dinitrobenzene (DNCB)-induced dermatitis, as evidenced by reduced skin lesion severity, lower dermatitis scores, and decreased epidermal thickening. Mechanistically, acetate attenuated allergic responses by binding to free fatty acid receptor 2 (FFAR2) and suppressing the Th2 pathway through GATA binding factor 3 downregulation, along with marked reductions in serum immunoglobulin E and thymic stromal lymphopoietin levels. Notably, acetate administration did not alter gut microbiota composition or relative abundances.ConclusionOur results revealed that the ratio of Bacteroidetes/Firmicutes and low levels of acetate play important regulatory roles in AD, and exogenous supplementation of acetate can alleviate DNCB-induced AD in mice through the FFAR2 and Th2 pathways. These findings provide valuable insights into the mechanisms of AD occurrence and progression, microbial community dynamics, metabolic regulation, and functional food innovation.